THE ACCOUNTING CONCEPT OF REALIZATION. - Windal, Floyd W. (The Accounting Review, 1961)
Abstract In addition to the criteria set forth above, additional sets could be given for the realization of a capital contribution, a capital withdrawal, an investment, a liability liquidation, and a loan. It is felt, however, that those presented illustrate adequately the type of criteria currently used in practice. There are, of course, some instances where they are not strictly followed. The criteria are not thereby discredited, however, they apply in the vast majority of situations, and the exceptions perhaps point to inconsistencies in accounting theory. It should be understood that the writer does not advocate that these criteria necessarily should be followed. They are merely those which seem currently to be in effect. The criteria presented embody the factors of measurability and permanence, and serve as guides to the accountant in determining if a change in an asset or liability is sufficiently definite and objective to warrant recognition in the accounts. It should perhaps be pointed out here that the sale and the purchase are often the signal to the accountant that certain criteria have been met. In the normal situation, the sale is the signal that revenue has been realized and the purchase is the signal that a cost has been realized. They merely serve as prime facie evidence, however, that specific criteria have been met. It can be seen that the judgment of the accountant plays an important part in all these criteria. He must reach conclusions in each case as to the degree of permanence and objectivity present. His decision, one way or the other, will determine whether or not a particular item is to be considered realized.